A literature review on future global mean sea level rise and ice sheet instability - Leijala, Ulpu; Särkkä, Jani; Johansson, Milla (Ilmatieteen laitos, 2025)
In this literature review, we familiarized with the most recent article on mean sea level projections for the Finnish coast (Pellikka et al., 2023), which takes into account the accelerating global mean sea level rise (GMSL) as well as the internal Baltic Sea characteristics (post-glacial land uplift and the Baltic Sea water balance). Considering the range of different emission paths, the following mean sea level change up to 2100 is expected on the Finnish coast: -40 cm to +10 cm for the Bothnian Bay, -40 cm to +40 cm for the Bothnian Sea, and 0 cm to +60 cm for the Gulf of Finland. Because of the large uncertainties, sea level rise exceeding one meter cannot be ruled out. In addition to the publication targeted for the Finnish coast, we reviewed 9 recent studies related to melting of the large ice sheets in Antarctica and Greenland, and their contribution to GMSL rise. These articles (Stokes et al., 2022; Hill et al., 2023; Reese et al., 2023; Grinsted et al., 2022; Bamber et al., 2022; van de Wal et al., 2022; Naughten et al., 2023; Horton et al., 2020; Box et al., 2022) utilized various methods, timespans and likelihood ranges, thus direct comparison between the study outcomes is not reasonable. However, we may summarize from the articles following larger-scale findings: 1) Future ocean warming and ice sheet melting in the Amundsen Sea area are expected to be markedly larger compared to the past behavior, 2) The West Antarctic Ice sheet (WAIS) is the main contributor to the global sea level rise by 2100, 3) Marine ice sheet instability (MISI) process is not ongoing currently in WAIS, 4) Western parts of Greenland are contributing to the sea level rise more than the eastern regions of the ice sheet, 5) Rates of sea level rise in projections based on models are smaller compared to the observed sea level rise rates, and 6) The most important uncertainty source related to GMSL rise projections is ice sheets, particularly the unknown response of Antarctica in a warmer globe.